2017
DOI: 10.1039/c6ra25557d
|View full text |Cite
|
Sign up to set email alerts
|

A novel synthetic approach to poly(hydrosiloxane)s via hydrolytic oxidation of primary organosilanes with a AuNPs-stabilized Pickering interfacial catalyst

Abstract: A simple and versatile approach based on AuNPs-stabilized Pickering catalyst in water–chloroform biphasic medium has been developed for the synthesis of poly(alkyl/arylhydrosiloxane)s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…With these materials the catalytic activity and selectivity in the hydrolytic oxidation of primary alkyl/aryl silanes was studied. 70 Recently, these principles even have been applied in an amplification in an enzyme-free visual immunoassay, again using the reaction of octadecylsilane. 71 A very interesting approach was reported by Morse and coworkers.…”
Section: Rsi(oh)mentioning
confidence: 99%
See 1 more Smart Citation
“…With these materials the catalytic activity and selectivity in the hydrolytic oxidation of primary alkyl/aryl silanes was studied. 70 Recently, these principles even have been applied in an amplification in an enzyme-free visual immunoassay, again using the reaction of octadecylsilane. 71 A very interesting approach was reported by Morse and coworkers.…”
Section: Rsi(oh)mentioning
confidence: 99%
“…The stabilization of gold nanoparticles with an amphiphilic block copolymer assists the organization of these nanoparticles at a water–chloroform interface. With these materials the catalytic activity and selectivity in the hydrolytic oxidation of primary alkyl/aryl silanes was studied …”
Section: Polymerizationmentioning
confidence: 99%
“…Also worthy of note is the comprehensive use of B­(C 6 F 5 ) 3 as the catalyst in the processes utilizing silanols , and alkoxysilanes. , That idea was subsequently developed by the Shimada group to synthesize a library of sequence-controlled oligosiloxanes via a one-pot procedure. Finally, Shankar et al. reported the conversion of hydrosilanes into poly­(siloxanes) mediated by gold and palladium nanoparticles. , In this context, the additional benefits related to one-pot procedures also need to be underlined. Higher efficiency, easier purification process, as well as higher yields are among them. In this paper, we present a highly chemoselective and efficient method for the dehydrogenative coupling of a variety of hydrosilanes with POSS silanols catalyzed by the commercially available and stable ruthenium dodecacarbonyl catalyst (Ru 3 (CO) 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…45−47 Finally, Shankar et al reported the conversion of hydrosilanes into poly(siloxanes) mediated by gold and palladium nanoparticles. 48,49 In this context, the additional benefits related to one-pot procedures also need to be underlined. 50−56 Higher efficiency, easier purification process, as well as higher yields are among them.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We suspect that the interaction between the exterior surface of the polymer may play a role in the formation of these novel shapes. The encapsulation of inorganic nanoparticles by polymer 1 adds up the library of polysiloxanes-stabilized nanoparticles [54][55][56]. Overall, the accommodation of different transition metal NPs is very attracting since they may find application in new catalysis reactions.…”
Section: Functional Group Variety and Application In Encapsulation Ofmentioning
confidence: 99%